2-Aminoimidazole borohydride as a hydrogen carrier. Issue 105 (31st October 2016) - Wu, Yong; Qi, Yue; Chen, Jun; Fu, He; Zheng, Jie; Li, Xingguo
Abstract : A novel hydrogen carrier, 2-aminoimidazole borohydride, was designed and synthesized. Abstract : 2-Aminoimidazole borohydride (Im-NH2 BH4 ) is synthesized via the reaction between 2-aminoimidazole hemisulfate ((Im-NH2 )2 SO4 ) and sodium borohydride by a simple ball milling method. This compound holds theoretical hydrogen capacity of 8.1 wt%. It is designed based on the strategy of destabilizating BH4 − using a large conjugated cation, Im-NH2 + and maximizing the protonic-hydridic hydrogen interaction by balancing their numbers. Thermal dehydrogenation analyses demonstrate that it can release about 3.2 wt% hydrogen (Na2 SO4 included) without gaseous impurities below 320 °C. The decomposition process has three exothermal steps and the onset dehydrogenation temperature is 50.5 °C. These results indicate that the above strategy is effective. The dehydrogenation process of this compound is discussed and the product at 320 °C is proposed to be C3 N3 H3 BH.